Toward an Ecologically Optimized N:P Recovery from Wastewater by Microalgae - Fernandes, Tânia V.; Suárez-Muñoz, María; Trebuch, Lukas M.; Verbraak, Paul J.; Van de Waal, Dedmer B. (Frontiers in Microbiology, 2017)
Global stores of important resources such as phosphorus (P) are being rapidly depleted, while the excessive use of nutrients has led to the enrichment of surface waters worldwide. Ideally, nutrients would be recovered from wastewater, which will not only prevent eutrophication but also provide access to alternative nutrient stores. Current state-of-the-art wastewater treatment technologies are effective in removing these nutrients from wastewater, yet they can only recover P and often in an insufficient way. Microalgae, however, can effectively assimilate P and nitrogen (N), as well as other macro- and micronutrients, allowing these nutrients to be recovered into valuable products that can be used to close nutrient cycles (e.g. fertilizer, bioplastics, colour dyes, bulk chemicals). Here, we show that the green alga Chlorella sorokiniana is able to remove all inorganic N and P present in concentrated toilet wastewater (i.e. black water) with N:P ratios ranging between 15 and 26. However, the N and P uptake by the algae is imbalanced relative to the wastewater N:P stoichiometry, resulting in a rapid removal of P but relatively slower removal of N. Here, we discuss how ecological principles such as ecological stoichiometry and resource-ratio theory may help optimize N:P removal and allow for more effective recovery of N and P from black water.